A structure-property study for konjac glucomannan and guar galactomannan: Selective carboxylation and scale inhibition. (1st January 2023) - Zhang, Kegui; Ge, Feng; Tang, Fukai; Tan, Lichao; Qiu, Yue; Zhu, Xinsheng
Abstract: The effect of structural difference for konjac glucomannan (KGM) and guar galactomannan (GGM) on their physicochemical properties including selective carboxylation, biodegradation and scale inhibition was firstly investigated. Compared with GGM, KGM can be specially modified by amino acid to prepare carboxyl-functionalized polysaccharides. The structure-activity relationship explaining the difference in carboxylation activity and the anti-scaling abilities of polysaccharides and carboxylated derivatives were explored by static anti-scaling, iron oxide dispersion and biodegradation tests coupled with structural and morphological characterizations. KGM with linear structure was preferred for carboxylated modification by glutamic acid (KGMG) and aspartic acid (KGMA) while GGM with branched structure failed to accomplish that due to steric hindrance. GGM and KGM showed limited scale inhibition performance, which was probably attributed to the moderate adsorption and isolation effect of macromolecular stereoscopic structure. While KGMA and KGMG performed as effective and degradable inhibitors for CaCO3 scale with inhibitory efficiencies > 90 %. Graphical abstract: Unlabelled Image Highlights: Konjac glucomannan shows selectivity on carboxylation compared with guar galactomannan. Konjac glucomannan and guar galactomannan have limited dispersing effect on CaCO3 scale. CaCO3 crystal is changed from cubic calcite to spherical vaterite by inhibitors. Theoretical research explains the structure-activity relationship of carbohydrate polymers.